2018
DOI: 10.1038/s41598-018-22533-0
|View full text |Cite|
|
Sign up to set email alerts
|

Organic osmolytes preserve the function of the developing tight junction in ultraviolet B-irradiated rat epidermal keratinocytes

Abstract: Epidermal barrier function is provided by the highly keratinised stratum corneum and also by tight junctions (TJs) in the granular layer of skin. The development of the TJ barrier significantly deteriorates in response to ultraviolet B radiation (UVB). Following exposure to UVB, keratinocytes accumulate organic osmolytes, which are known to preserve cell volume during water stress. Since TJs are intimately associated with control of water homeostasis in skin, we hypothesised that there may be a direct influenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
15
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 80 publications
(88 reference statements)
0
15
1
Order By: Relevance
“…There was no apparent change in CLDN4 localization, but the amount of CLDN4 protein increased transiently after 6 h of H 2 O 2 treatment. Recently, El-Chami et al [27] reported that H 2 O 2 (1 mM, a higher concentration than in our study) induced the mislocalization of CLDN1, CLDN4, and occludin in a continuous cell line of rat epidermal keratinocytes. We suggest that oxidative stress selectively induces the mislocalization of CLDN1 in low-level cell toxic conditions.…”
Section: Discussioncontrasting
confidence: 42%
“…There was no apparent change in CLDN4 localization, but the amount of CLDN4 protein increased transiently after 6 h of H 2 O 2 treatment. Recently, El-Chami et al [27] reported that H 2 O 2 (1 mM, a higher concentration than in our study) induced the mislocalization of CLDN1, CLDN4, and occludin in a continuous cell line of rat epidermal keratinocytes. We suggest that oxidative stress selectively induces the mislocalization of CLDN1 in low-level cell toxic conditions.…”
Section: Discussioncontrasting
confidence: 42%
“…All these processes can potentially affect and modulate TJ proteins. Interestingly, taurine, one of these osmolytes, has been shown to enhance the TJ barrier in different epithelia (El-Chami et al, 2018). Interestingly, taurine, one of these osmolytes, has been shown to enhance the TJ barrier in different epithelia (El-Chami et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, an increase in extracellular osmolality can lead to a longterm increase in cytoplasmic osmolytes, as a compensatory process to preserve cell volume (Alfieri and Petronini, 2007). Interestingly, taurine, one of these osmolytes, has been shown to enhance the TJ barrier in different epithelia (El-Chami et al, 2018). Assessment of all these potential mechanisms of regulating TJ under hyperosmolarity is an attractive area for future research.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, El-Chami et al [ 29 ] reported that a single dose of UVB (10 mJ/cm 2 ) induces the elevation of ROS and disruption of the TJ barrier in rat epidermal keratinocyte. Our results indicated that the total amount of CLDN1 protein is constant for 24 h, but CLDN1 dissociates from the TJ ( Figure 1 ).…”
Section: Discussionmentioning
confidence: 99%